2015
DOI: 10.1112/jtopol/jtv026
|View full text |Cite
|
Sign up to set email alerts
|

The Farrell–Jones conjecture for virtually solvable groups:

Abstract: Abstract. We prove the K-and L-theoretic Farrell-Jones Conjecture (with coefficients in additive categories) for virtually solvable groups.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 23 publications
0
65
0
Order By: Relevance
“…Then p −1 (V ) ∼ = F n+1 ⋊V is a hyperbolic group. Thus it satisfies the K-FJCw ( [3], [16]). The result follows from Remark 2.1.…”
Section: The Lower K-theory For H (N)mentioning
confidence: 99%
See 1 more Smart Citation
“…Then p −1 (V ) ∼ = F n+1 ⋊V is a hyperbolic group. Thus it satisfies the K-FJCw ( [3], [16]). The result follows from Remark 2.1.…”
Section: The Lower K-theory For H (N)mentioning
confidence: 99%
“…In [16], it was shown that CAT(0)-groups satisfy the K-FJCw. That means that finite extensions of CAT(0)-groups satisfy the K-FJCw.…”
Section: Preliminaries and Notationmentioning
confidence: 99%
“…For example, by work of Kammeyer-Lück-Rüping [44] all lattice in Lie groups satisfy the Farrell-Jones Conjecture; despite Lafforgues [51] positive results for many property T groups, the Baum-Connes Conjecture is still a challenge for SL 3 (Z). Wegner [77] proved the Farrell-Jones Conjecture for all solvable groups, but the case of amenable (or just elementary amenable) groups is open; in contrast Higson-Kasparov [41] proved the Baum-Connes Conjecture for all a-T-menable groups, a class of groups that contains all amenable groups. On the other hand, hyperbolic groups satisfy both conjectures.…”
mentioning
confidence: 99%
“…The reader should have in mind that it is known for a large class of groups, e.g., hyperbolic groups, CAT(0)-groups, solvable groups, lattices in almost connected Lie groups, fundamental groups of 3-manifolds and passes to subgroups, finite direct products, free products, and colimits of directed systems of groups (with arbitrary structure maps). For more information we refer for instance to [1,2,3,14,25,41,51]. Theorem 6.7 (Basic properties of the V -twisted L 2 -torsion for finite free G-CW -complexes).…”
mentioning
confidence: 99%